PATTERN OF HARMFUL PRACTICES TOWARDS THE NEWBORN IN A PAKISTANI COMMUNITY: Harmful Practices in Newborn in a Pakistani Community - Saeed, Surg Captain Afzal; Affzal, Tasneem; Hassan, Maqsood Ul (Pakistan Armed Forces Medical Journal, 2010)
Objectives: To assess the pattern of harmful practices which can affect the neonatal mortality in our community. Study design: It was a cross-sectional study based on recall of child birth and rearing events by the respondents. Place and Duration of the Study : The study was carried out in Union Council 45 (UC 45) of Rawalpindi District, which had a population of 25000 people with mostly low income families living on either side of Nalla Lai. The survey was carried out 20th July to 20th September 2006. Material and Method: One hundred mothers were interviewed. A questionnaire was used to identify these practices in an urban setting. Results: It was found that many harmful neonatal practices were prevalent in the study population most common being the powder sprinkling on the baby (94%), removal of vernix caseosa (81%), pre-lacteal feeding (79%), unhygienic cord practices (74%), and application of contaminated Surma (73%). Moreover mothers are mostly unaware of the consequences of their practices, however, they were found receptive and eager to know whether their practices were beneficial or not. Conclusion: The study highlights that many harmful neonatal practices are prevalent in the society. Larger study is required to determine the quantum effect of traditional harmful neonatal practices to the newborn mortality in order to prioritize our actions and develop strategies.